2020
DOI: 10.1101/2020.01.08.897595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomics Dissection of Cardiac Protein Profiles of Humans and Model Organisms

Abstract: The study of human cardiac pathologies often relies on research conducted in model organisms to gain molecular insight into disease and to develop novel treatment strategies; however, translating findings from model organisms back to human can present a significant challenge, in part due to a lack of knowledge about the differences across species in cardiac protein abundances and their interactions. Here we set out to bridge this knowledge gap by presenting a global analysis of cardiac protein expression profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It is useful in qualitative and quantitative analyses of disease biomarkers in various specimens that lead to not only diagnosis but also risk stratification and guidance in the selection of therapeutic modalities [64]. Linscheid et al recently performed systematic analyses of cardiac proteomes across cardiac chambers in humans, pigs, and four commonly used animal models and identified and quantified approximately 7,000 proteins, comparing them with respect to cardiac function and mechanisms of diseases [65]. Tamiyakul et al performed a proteome analysis on the myocardium of the DMD pig model that showed an altered abundance of several proteins such as reduction of myosin-6, which is directly involved in muscle contraction [66] and validated the results by complementary mass spectrometry [67].…”
Section: Future Directions Of Large Animal Model-based Cardiovascular...mentioning
confidence: 99%
“…It is useful in qualitative and quantitative analyses of disease biomarkers in various specimens that lead to not only diagnosis but also risk stratification and guidance in the selection of therapeutic modalities [64]. Linscheid et al recently performed systematic analyses of cardiac proteomes across cardiac chambers in humans, pigs, and four commonly used animal models and identified and quantified approximately 7,000 proteins, comparing them with respect to cardiac function and mechanisms of diseases [65]. Tamiyakul et al performed a proteome analysis on the myocardium of the DMD pig model that showed an altered abundance of several proteins such as reduction of myosin-6, which is directly involved in muscle contraction [66] and validated the results by complementary mass spectrometry [67].…”
Section: Future Directions Of Large Animal Model-based Cardiovascular...mentioning
confidence: 99%